Legal Views for Orphans Abused by Foster Parents - Debora K Nayoan; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
The aim of legal protection for children is to protect children's basic freedoms and opportunities from various interests that have an interest in their welfare. Child welfare refers to a way of life that ensures children receive normal physical, spiritual and social development. Due to various challenges, not all parents are able to recognize the welfare of their children. Legal protection for children is regulated in several statutory regulations, namely in Law Number 17 of 2016 concerning the Determination of Perppu Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Welfare. Children are one of the key elements in the creation of legal arrangements in Indonesia.